Analisis Swot Dalam Pembuatan Program relationship Marketing Pada Share Tea Sun Plaza Medan - Ika Apia Septira (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2020)
The purpose of this research is to design and find out the relationship marketing strategy at Share Tea Sun Plaza Medan. The analytical method used is descriptive analysis (qualitative), triangular method, internal matrix factor (IFE), external matrix factor (EFE), and strength, weakness, opportunity and threat (SWOT) matrix to create Relationship Marketing for Share Tea Sun Plaza program Field. The results of the study at Share Tea Sun Plaza Medan by using a matrix of internal and external factors and using a SWOT analysis, a marketing relationship strategy program can be produced consisting of a Fresnack Card, Bigday Sale, and a Fresfum Card that will be used in relational marketing. Keywords: Strengths, Weaknesses, Opportunities, Threats, Marketing Relations